BARRIERS AND ENCOURAGEMENTS OF CHILDLESSNESS IN INDONESIA - Kumala, Thea (BESTARI BPS Kalimantan Timur, 2025)
Childlessness discourse is interesting and important to discuss since it has become a phenomenon, not only in developed countries but also in the developing world. Specifically, being childfree as a willing decision of childlessness has become pervasive in Indonesia. Indonesia is a country where cultures promote stigmas, which contradict the choice of childlessness which is now valued as the freedom to act and live. This study examines how the community is affected by the interpretation of childlessness by measuring its barriers and encouragement. We applied primary data collected using a survey questionnaire collected from 430 adults living in Jakarta, Indonesia, and adopted Likert scale questions as human attitude measure variables. We used a multinomial logit logistic regression model to estimate the characteristics of respondents who choose to be childless. The result showed that family pressures are the main barriers to childless behavior, while the childfree movement, Western influence, and freedom become prominent encouragements.